Economic and virtual water multilayer networks in China. (25th December 2022) - Wang, Junren; Konar, Megan; Dalin, Carole; Liu, Yu; Stillwell, Ashlynn S.; Xu, Ming; Zhu, Tingju
Abstract: Supply chains are complex systems that can be conceptualized as networks. Several studies have examined the structural properties of economic networks (i.e., given in units of financial value) and virtual water supply chain networks (i.e., where economic connections are reported in terms of their embodied water). In both cases, connections both within and between economic sectors are important to fully represent structural network properties, highlighting the importance of multilayer network analyses. The similarities and differences between economic and virtual water multilayer networks are yet to be well understood. The goal of this study is to consistently compare the economic and virtual water multilayer networks within China. Environmentally extended multi-regional input–output (EE-MRIO) data is used to build multilayer networks between 31 provinces and 41 economic sectors (nodes are province-sectors) for commodities and services in the year 2017, using both economic [¥] and virtual water [m 3 ] weights. This study shows that virtual water multilayer networks are relevant to address questions of water sustainability, scarcity, and hazards in supply chains, but that examining virtual water networks in isolation may not identify the economically important core nodes. Consideration of both economic and embedded resource networks could enhance our understanding of complex supply chains. Highlights: Economic and virtual water multilayer networks are highly connected and heterogeneous. Agriculture is the most central sector in China's virtual water multilayer. The central nodes in virtual water and economic multiplex networks show little overlap.